2016
DOI: 10.1177/1057083715619963
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Students to Consider Music Education as a Future Profession

Abstract: The purpose of this study was to examine the attitudes, communication, and opportunities provided by music teachers to encourage consideration of the music teaching profession. Survey participants (N = 436) were music educators from the Southeast (235), Midwest (51), and Southwest (149) National Association for Music Education regions of the United States. Fifty-two percent of respondents reported encouraging students to explore the music teaching profession, one third reported uncertainty about their encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Try to just be the best teacher that I can be” (Interview 2). Her less aggressive approach corroborates those found by other researchers (e.g., Porter et al, 2017) but runs counter to popular music education advocacy efforts designed for broad appeal, such as flyers posted in public, web advertisements, or mass email messages. However, taking into consideration Ms. Dana’s background in music therapy as well as music education, it is not surprising that she views collegiate music study as consisting of more options than music education.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Try to just be the best teacher that I can be” (Interview 2). Her less aggressive approach corroborates those found by other researchers (e.g., Porter et al, 2017) but runs counter to popular music education advocacy efforts designed for broad appeal, such as flyers posted in public, web advertisements, or mass email messages. However, taking into consideration Ms. Dana’s background in music therapy as well as music education, it is not surprising that she views collegiate music study as consisting of more options than music education.…”
Section: Resultssupporting
confidence: 78%
“…In-service music educators have indicated that they initially entered the music education profession because they became inspired by events at state music education associations (MEAs; Councill et al, 2013), wanted to contribute to specific communities (Eros, 2018), and, as found most frequently across the literature, were heavily influenced by their school and private studio music teachers (Cox, 1994; Gardner, 2010; Hamann & Walker, 1993; Pellegrino & Millican, 2014; Rickels et al, 2019). In-service teachers have continued to encourage their students to consider a career in music education, sometimes despite their own frustration with professional issues (Porter et al, 2017), which lends credence to the idea that in-service music teachers remain vital to recruitment efforts in music education.…”
Section: Related Literaturementioning
confidence: 99%
“…Even those offering studio instruction as a second career recalled positive interactions with or reported support or encouragement from former and current musical mentors (Taylor & Hallam, 2011). Porter et al (2017) examined the student experiences and types of support provided by in-service music educators and found that more than half of survey respondents actively and purposefully shared their personal career choice story with students and/or offered them encouragement to seek an occupation in the field of teaching.…”
Section: Music Teacher Influencementioning
confidence: 99%
“…Teachers in P–12 should also be aware of how their overt and covert messaging about music careers may be perceived in combination with these experiences. Porter et al (2017) noted that there was a trend among some current music teachers to purposefully not encourage their students to consider music teacher education, or in some cases even to discourage it, due to concerns about the current perceptions of and realities in the music teaching profession. In addition to the known role that music teachers, parents, relatives, and siblings play in student career selection, we should not discount the influence of non–music teachers and school counselors who might further speak positively of the profession.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation